2018
DOI: 10.5812/ijem.84750
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lipids During 20 Years in the Tehran Lipid and Glucose Study: Prevalence, Trends and Impact on Non-Communicable Diseases

Abstract: ContextDyslipidemia, including elevated serum total cholesterol (TC), low density lipoprotein cholesterol (LDL-C), and triglycerides (TG), and low high density lipoprotein cholesterol (HDL-C) is a major modifiable risk factor for non-communicable diseases (NCDs). This review summarizes many of the key findings on lipid measures in the Tehran lipid and glucose study (TLGS), a large scale community-based study with an approximately two decade follow-up.Evidence AcquisitionA systematic literature search was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 35 publications
4
14
0
Order By: Relevance
“…We showed a 2-fold rise in IFG, from 7% in 1999 to The favorable trend in lipid profiles and blood pressure, despite increasing levels of general and central adiposity in our study population has also been shown in previous studies conducted among Iranian adolescents. [25][26][27][28] This trend might be a consequence of a regulatory program designed by the Ministry of Health [29][30][31] to limit the consumption of salt, fat in general as well as trans-fatty acids (TFA).…”
Section: Discussionmentioning
confidence: 99%
“…We showed a 2-fold rise in IFG, from 7% in 1999 to The favorable trend in lipid profiles and blood pressure, despite increasing levels of general and central adiposity in our study population has also been shown in previous studies conducted among Iranian adolescents. [25][26][27][28] This trend might be a consequence of a regulatory program designed by the Ministry of Health [29][30][31] to limit the consumption of salt, fat in general as well as trans-fatty acids (TFA).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the high prevalence of dyslipidemia, obesity, and unhealthy lifestyle in Iran, lipid profile has a favorable trend. This control of lipids is mainly explained by lower consumption of saturated and hydrogenated oil and higher usage of liquid oil, implemented by the government [ 47 , 48 ]. More public education and screening plans for intermediate- and high-risk groups are needed to control this risk factor effectively.…”
Section: Review Of the Major Risk Factorsmentioning
confidence: 99%
“…Risk factors for cardiovascular disease (CVD) are higher than women of childbearing age. Appropriate lifestyle changes can prevent from CVD such as healthy diet, quitting smoking, regular exercise and maintaining proper weight (Baghbani-Oskouei, Tohidi, Asgari, Ramezankhani, Azizi & Hadaegh, 2018;Colpani, et al, 2018;Ford, Zhao, Tsai & Li, 2011;Gurka, Vishnu, Santen & DeBoer, 2016;Hashemi Nazari, Shakiba , Khalili, Hadaegh, Tohidi & Azizi, 2015;Hunter, Hardy, Norton & Griffiths, 2016;Palacios et al, 2010;Mc Sweeney et al, 2016;Muka et al, 2016;Mumusoglu & Yildiz, 2019;Nejat et al, 2014;Tabatabaei-Malazy et al, 2018). Several studies have shown that in postmenopausal women "excess waist circumference or abdominal obesity", "overweight and obese" hypertension, dyslipidemia, hyperglycemia, and high abdominal obesity rates are closely related to the prevention and treatment of CVD and health promotion.…”
Section: Perimenopaual Is High Risk Factor For Cardiovascular Diseasementioning
confidence: 99%